Presence of HLA-B27 is associated with changes of serum levels of mediators of the Wnt and hedgehog pathway - Aschermann, Sarah; Englbrecht, Matthias; Bergua, Antonio; Spriewald, Bernd M.; Said-Nahal, Rhula; Breban, Maxime; Schett, Georg; Rech, Juergen (Joint Bone Spine, 2016)
HLA-B27 is present in 5% of the Caucasian population and is strongly associated with the development of spondyloarthritis (SpA), a disease characterized by inflammation and substantial bone changes. We hypothesized that the presence of HLA-B27 in itself is associated with alterations of key regulatory of bone homeostasis.Sera of 241 individuals were assessed for the serum levels of Wnt pathway regulators, sclerostin and dickkopf (Dkk)-1 as well as Indian hedgehog (IHH) and collagen type I cleavage products (CTX1). Of the 151 HLA-B27+ subjects, 31 had SpA, 30 had anterior uveitis, 30 were healthy individuals and 60 healthy siblings of patients with SpA.Sclerostin levels were significantly (P<0.001) lower in HLA-B27+ subjects (314±21pg/mL) compared to HLA-B27 negative controls (mean±SEM: 492±30pg/mL), no matter if subjects were either healthy, or affected by SpA or uveitis. Similar results were found for Dkk-1. No differences between the groups with respect to the bone resorption marker CTX1 were found. In contrast, IHH levels were significantly (P<0.001) higher in the carriers of HLA-B27 than in the negative controls.Changes in key regulators of the Wnt pathway as well as IHH, a molecule regulating endochondral ossification, are found in HLA-B27 carriers, independent if they were healthy or affected by uveitis or SpA.
EVALuna2:13168

The pro and anti-inflammatory activities of immunoglobulin G - Lux, Anja; Aschermann, Sarah; Biburger, Markus; Nimmerjahn, Falk (Annals of the Rheumatic Diseases, 2010)
Immunoglobulin G (IgG) molecules are a family of glycoproteins essential for defending the body against invading pathogens. The antibody constant domain is very potent in initiating proinflammatory pathways such as the activation of innate immune effector cells via cellular receptors specific for the antibody constant region (Fc receptors) and the activation of the complement pathway. During autoimmune disease the normally protective antimicrobial function of these molecules is targeted to healthy tissues often with disastrous consequences. Interestingly, one successful anti-inflammatory therapy for many autoimmune diseases is the infusion of high doses of IgG molecules, the so-called intravenous IgG therapy. How one class of molecules can have such opposing functions will be the major focus of this review.